2014
DOI: 10.1080/15022250.2014.887609
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Acquisition and Assimilation in Tourism-Innovation Processes

Abstract: The paper develops a framework and an understanding of the external knowledge absorption in nature-based tourism companies. The concept of potential absorptive capacity is the starting point for exploring how external knowledge (tacit and explicit) is absorbed and assimilated in tourism innovation processes. Although knowledge is the engine that drives innovation, tourism firms can have problems and challenges when trying to absorb external knowledge for innovation. The main challenge is to access and absorb t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 45 publications
1
79
0
4
Order By: Relevance
“…Innovative idea formation will then be followed by a continuous innovation development process, which involves several determinants. Hoarau demonstrated that small-and medium-sized whale-watching firms can absorb knowledge from scientists and customers to generate innovation [51]. Furthermore, the tourism industry is a labor-intensive industry.…”
Section: Driving Forces Of Innovation In Mses and Smesmentioning
confidence: 99%
“…Innovative idea formation will then be followed by a continuous innovation development process, which involves several determinants. Hoarau demonstrated that small-and medium-sized whale-watching firms can absorb knowledge from scientists and customers to generate innovation [51]. Furthermore, the tourism industry is a labor-intensive industry.…”
Section: Driving Forces Of Innovation In Mses and Smesmentioning
confidence: 99%
“…Tour guides are the critical members in tourism industry and their services are mainly based on their professional competencies (Chen et al, 2012;Hoarau, 2014;Mao & Wang, 2010). When guiding the tour groups, they must have broad tourism related knowledge in order to satisfy different tourists' needs (Çetı̇nkaya & Öter, 2016).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Taka ocena, w dotychczasowych badaniach, oparta była na opinii jednej osoby, znaczenie zdolności do absorpcji w przedsiębiorstwach turystycznych Dotychczasowe badania prowadzone w przedsiębiorstwach turystycznych sugerują, że zdolność od absorpcji wiedzy może być istotnym czynnikiem wpływającym na wyniki przedsiębior-stwa. Badacze testowali zarówno bezpośrednie związki pomiędzy zdolnością do absorpcji wiedzy a wynikami przedsiębiorstw (Herath, Mahmood, 2014), jak również pośredni wpływ na wyniki poprzez wzrost innowacyjności przedsiębiorstw (Hoarau, 2014) oraz zdolności do uczenia się (Brookes, 2014).…”
Section: Istota I Znaczenie Zdolności Do Absorpcji Wiedzyunclassified
“…Dotychczasowe badania wśród przedsiębiorstw turystycznych opierają się na skalach opracowanych dla innych rodzajów działalności gospodarczej. Jest to postulat wysuwany także przez Hoarau (2014).…”
Section: Istota I Znaczenie Zdolności Do Absorpcji Wiedzyunclassified